The development and validation of a scale measuring mobile phone use in an academic environment - Nehir Yasan Ak; Soner Yıldırım (International Journal of Assessment Tools in Education)
The purpose of this study was to fill the gap in current research on educational mobile phone use within the framework for the rational analysis of the mobile education (FRAME) model. The paper developed and validated the Mobile Phone Use in Academic Environment Scale (MPUAES) to measure both positive and negative aspects of educational use of mobile phones. The data was collected from all faculties and all grade levels of Middle East Technical University in Ankara. The inclusion criterion for the participation in the study was owning a smartphone. The exploratory and confirmatory factor analyses were run with two different groups in a total of 1887 undergraduate students. Three factors structure with 18 items were obtained, which were labeled as facilitator, distractor, and connectedness. These three factors explained 63.42% of the total variance. For confirmation of the factor structure, confirmatory factor analysis was performed with the second sample. The Cronbach alpha coefficient of each factor ranged between .90 and .74. To conclude, the findings of the study proposed that the scores obtained from the developed scale were valid and reliable in measuring undergraduate students’ mobile phone use in an academic environment.